Scientific impact of presentations from the EURAPS and the AAPS meetings: A 10-year review. Issue 1 (January 2017) - Khorasani, Hoda; Lassen, Mats Højbjerg; Kuzon, William; Bonde, Christian
Summary: Introduction: Presentation at scientific meetings is the usual first step to communicate new research findings. However, without subsequent, peer-reviewed publication, the wider propagation and the permanent documentation of important scholarly work may be lost. Our aim was to analyze and compare the publication status of the work presented at the European Association of Plastic Surgeons' (EURAPS) and at the American Association of Plastic Surgeons' (AAPS) annual meetings. Materials and methods: By using the abstract booklets from the annual meetings, all presentations given over a 10-year period (2000–2009) were analyzed. A search using PubMed and Google Scholar was performed to obtain publication status of each presentation as of 2014 (observation period: 5 years). Data were analyzed according to subspecialty. Weighted chi-square was used to examine differences in publication rates for the two societies and for English speaking vs. non-English speaking countries. Results: Seventy-two percent (n = 246) of the abstracts from the AAPS were published in peer-reviewed journals. The most published subspecialty was "Craniofacial surgery" followed by "Breast surgery." Mean time to publication was 22.1 months (range -72–111 months). The most common journal for publication was Plastic and Reconstructive Surgery (PRS). Sixty-seven percent (n = 449) of the EURAPS abstracts were published in peer-reviewed journals. The most published subspecialty was "Microsurgery" followed by "Clinical studies." The mean time to publication was 17.3 months (range -67–111 months). The most common journal for publication was PRS. Differences between the two societies' publication status were not observed (p = 0.157), but EURAPS abstracts had a significantly shorter time to publication (p = 0.007). Differences between English-speaking and non-English-speaking countries were not observed (p = 0.931). Mean level of evidence for published studies from the AAPS and the EURAPS meetings was 3.5 and 3.7, respectively. Conclusion: A majority of the presented abstracts from both societies have resulted in publication. After "The Society for Cardiothoracic Surgery, " AAPS and EURAPS have the highest publication rates for surgical abstracts, indicating a high scientific value of these meetings.